AN ANALYSIS OF THE SECOND YEAR STUDENTS’ SPEAKING ABILITY IN DEBATE AT THE ENGLISH DEPARTMENT OF BUNG HATTA UNIVERSITY - Adzanil Prima Septy; Sri Utari Riri Putri Sofiani (Universitas Bung Hatta, 2022)
The purpose of this research was to describe the second-year students’ speaking ability in the debate. The descriptive method was used as the design of this research. The population of this research was the second-year students at the English Department of Bung Hatta University who registered in the academic year 2020/2021. The researcher used the total sampling technique to select the sample, and the number of sample members was 37 students. The instrument for collecting the data in this research was a speaking test in the form of debate. To identify if the test is reliable, the researcher used the inter-rater method that two scorers checked the students’ speaking performance. The result of the analysis showed that the test was reliable. It was supported by the fact that the coefficient correlation is 0.89. It was categorized as a very high correlation. Then the last was valid in terms of contents because it had covered all materials that students had learned. Generally, the result of this research showed that the students’ speaking ability in debate at the English Department of Bung Hatta University was very high. In general, the students’ speaking ability in the debate was classified as very high ability. This research concludes that the second-year students’ speaking ability in debate at the English Department of Bung Hatta University was very high. REFERENCES Atchison, J. (2017). The Art of Debate. Virginia: The Great Courses. Bailey, K. (2016). Practical English Language Teaching Speaking. New York: The Mc. Graw Hill Companies. Chania, S., & Amri, Z. (2019). An Analysis of Students’ Grammatical Errors on Speaking at SEA Debate at English Department of Faculty of Languages and Arts of Universitas Negeri Padang. Journal of English Language Teaching, Vol. 8, No. 4. Claudia, A. (2017). An Analysis of The Second Year Students’ Speech Ability at the English Department of Bung Hatta University. Unpublished Thesis. Padang: Bung Hatta University. Fauzan, U. (2014). The Use of Improvisations Technique to Improve the Speaking Ability of EFL Students. Dinamika Ilmu, Vol. 14, No. 2. Lestari, L. F. (2018). Debate Technique as Teacher’s Strategies in Improving Students’ Higher Education English Speaking Skill. Musfirah. (2017). The Effectiveness Of Debate Method To Improve Students’ Speaking Skill. Didaktika Jurnal Kependidikan, Vol. 11, No. 2. Rasyid, A.R., Perdana, I., & Dayu, A.T. (2020). Students’ Speaking Achievement: The Application of Debate Technique For Teaching. Proceedings of Shepo 2020. Refnita, L. (2018). Educational research: A guide for Beginners. Padang: LPPM Universitas Bung Hatta. Rubiati, R. (2010). Improving Students’ Speaking Skill Through Debate Technique. IAIN Walisongo Semarang.